Fundamental study of the ultrasonic induced degradation of the popular antihistamine, diphenhydramine (DPH). (1st November 2018) - Cui, Danni; Mebel, Alexander M.; Arroyo-Mora, Luis E.; Zhao, Cen; De Caprio, Anthony; O'Shea, Kevin
Abstract: Diphenhydramine (DPH) the active ingredient in Benadryl, has been detected in streams, rivers and other surface water sources. As a bioactive compound, DPH impacts human health even at low concentrations. Ultrasonic irradiation at 640 kHz leads to the rapid degradation of DPH in aqueous solution. Radical scavenging experiments and detailed product studies indicate the DPH degradation involves direct pyrolysis and degradation reactions mediated by the hydroxyl radicals produced during cavitation. The degradation can be modeled by pseudo-first order kinetics yielding rate constants k of 0.210, 0.130, 0.082, 0.050, 0.035, 0.023 min −1 at the initial concentrations of 2.8, 5.2, 13.9, 27.0, 61.0, 160.0 μmol L −1, respectively. The degradation process follows the Langmuir-Hinshelwood (heterogeneous) model with a partition coefficient, KL-H = 0.06 μmol·L −1 and reactivity constant kr = 1.96 μmol min −1 ·L −1 . A competition kinetic study conducted employing the hydroxyl radical trap, coumarin, illustrates that DPH was degraded primarily by hydroxyl radical mediated processes. Computational studies employing Gaussian 09 basis set provide fundamental insight into the partitioning of the reaction pathways and the degradation mechanisms. The study demonstrates the ultrasonic degradation of DPH is rapid, follows simple kinetic expressions and is accurately modeled using computational methods. Graphical abstract: Image 1 Highlights: Ultrasonic degradation of diphenhydramine. Products studies. Modeling. Computational results.